2008
DOI: 10.1176/ps.2008.59.8.860
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Integrating Mental and General Health Services on Mental Health's Share of Total Health Care Spending in Alberta

Abstract: Despite concerns expressed before the transfer by federal and provincial reports over the level of expenditures devoted to mental health care, the integration of mental health services with other health services did not result in an increase of the share for mental health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Although prior research has found that the cost of managing schizophrenia is higher than other chronic diseases, 35 our findings suggest that the direct costs of schizophrenia are expanding at a greater rate than overall healthcare spending in the province. Mental health spending has historically been underrepresented in healthcare budgets 36 so at first glance increased spending on patients is promising. However, spending per capita remained stagnant over the 10-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior research has found that the cost of managing schizophrenia is higher than other chronic diseases, 35 our findings suggest that the direct costs of schizophrenia are expanding at a greater rate than overall healthcare spending in the province. Mental health spending has historically been underrepresented in healthcare budgets 36 so at first glance increased spending on patients is promising. However, spending per capita remained stagnant over the 10-year period.…”
Section: Discussionmentioning
confidence: 99%